TLR7 promotes smoke-induced experimental lung damage through the activity of mast cell tryptase - Liu, Gang; Haw, Tatt Jhong; Starkey, Malcolm R.; Philp, Ashleigh M.; Pavlidis, Stelios; Nalkurthi, Christina; Nair, Prema M.; Gomez, Henry M.; Hanish, Irwan; Hsu, Alan CY.; Hortle, Elinor; Pickles, Sophie; et al. (Nature Publishing, 2023)
Toll-like receptor 7 (TLR7) is known for eliciting immunity against single-stranded RNA viruses, and is increased in both human and cigarette smoke (CS)-induced, experimental chronic obstructive pulmonary disease (COPD). Here we show that the severity of CS-induced emphysema and COPD is reduced in TLR7-deficient mice, while inhalation of imiquimod, a TLR7-agonist, induces emphysema without CS exposure. This imiquimod-induced emphysema is reduced in mice deficient in mast cell protease-6, or when wild-type mice are treated with the mast cell stabilizer, cromolyn. Furthermore, therapeutic treatment with anti-TLR7 monoclonal antibody suppresses CS-induced emphysema, experimental COPD and accumulation of pulmonary mast cells in mice. Lastly, TLR7 mRNA is increased in pre-existing datasets from patients with COPD, while TLR7 + mast cells are increased in COPD lungs and associated with severity of COPD. Our results thus support roles for TLR7 in mediating emphysema and COPD through mast cell activity, and may implicate TLR7 as a potential therapeutic target.